Analisis Kritis Permasalahan Humanisasi Ilmu Agama - Asep Suraya Maulana (Jurnal Hikmatuna, 2018)
Islam was born as a religion in the middle of the socio-cultural of Arab society full of dynamics and social problematics. Discrimination and crime continue to blanket the lives of people at that time. Islam as a living system containing several sub-systems of aspects, and among them is a sub-system in the education sector. Through aspects of doctrine and education, Islam asserts that the urgency of science has never looked at economic, social and even racial differences. Speaking of the world of education, especially education in Indonesia today has faced various problems and challenges very heavy. Among the challenges are, cultural, ethical and moral globalization, as a result of technological advances (transport and information), and low levels of social-capital, low quality of education in Indonesia, and national macro issues, involving multidimensional crises in both fields economic, political, moral, cultural and so forth. In addition, there is an indication that the world of Islamic education is failing, which failed to humanize human (humanization), failed to form human in accordance with the vision and mission of creation. This failure has implications for the process of maternalistic education, away from Islamic values and weak character.